2017
DOI: 10.2147/bctt.s131334
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of steroid receptors by epigallocatechin-3-gallate in breast cancer cells

Abstract: It has been reported that phytoestrogen epigallocatechin gallate (EGCG) suppresses cancer cell proliferation and may have antitumor properties. In this study, we analyzed the effects of EGCG on estrogen receptor α (ERα) and progesterone receptor in hormone-dependent T-47D breast cancer cells. Western blot analysis revealed EGCG induced a concentration-dependent decrease in ERα protein levels, with a 56% reduction occurring with 60 µM EGCG when compared to controls. Downregulation of ERα protein levels was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…It was demonstrated in various studies that EGCG and quercetin exhibit anticancer activity. Besides steroid receptor (9) and PPARγ receptor (10) interaction, other assumed mechanisms of action include interaction with the PI3K/Akt/mTOR signaling pathway (11), VEGF (12), the the 67-kDa laminin receptor (67-LR) (13), p53, Bax protein (14) and Bcl-2 (15).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated in various studies that EGCG and quercetin exhibit anticancer activity. Besides steroid receptor (9) and PPARγ receptor (10) interaction, other assumed mechanisms of action include interaction with the PI3K/Akt/mTOR signaling pathway (11), VEGF (12), the the 67-kDa laminin receptor (67-LR) (13), p53, Bax protein (14) and Bcl-2 (15).…”
Section: Introductionmentioning
confidence: 99%
“…Such a difference could be related to the molecular characteristics of cells as well as the compounds characteristics, particularly variation in the cell ability to deal with estrogen, progesterone and androgen activities modulated by the compounds tested (Figure 12). It is postulated that some types of CATs have binding affinity for ERβ, ERα, PR and/or AR and could exhibit similar effects to that of selective modulators of hormone receptors, such as ER modulators (SERMs) [66][67][68][69][70], selective estrogen down-regulators (SERDs) [71][72][73], selective progesterone receptors modulators (SPRMs) [72] and selective androgen receptor modulators (SARMs), even in androgen-independent PC [74,75]. Furthermore, it is suggested that CATs can inhibit different enzymes involved in estrogen and androgen synthesis such as aromatase (aromatase inhibitors (AIs)] [76][77][78][79]) and 5α-reductase [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is suggested that some CATs act as ER down-regulators [71][72][73], particularly through ERα36 in TNBC progenitor cells [84]. In addition, it is suggested that some CATs can indirectly down-regulate ERα [73] via PR [72] in MCF-7 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, high concentrations promote processes such as apoptosis or cell cycle blockage resulting in antitumor effects as mentioned above. In addition, ER expression is also regulated by some polyphenols, for example, EGCG, which downregulates ER-α protein, mRNA and gene promoter activity in MCF-7 [ 198 ] and ER and PR in T-47D [ 199 ] cell lines. There are so many additional examples of flavonoids, like apigenin, luteolin myricetin, anthocyanidins or quercetin, and other compounds, such as stilbenes, ellagitannins, sulforaphanes, curcuminoids and tocopherols, among others, that are extensively reviewed [ 197 , 200 ].…”
Section: Breast Cancer Signatures and Polyphenolsmentioning
confidence: 99%